2023
DOI: 10.1007/s00216-023-04613-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of guanidine derivatives as representative persistent and mobile organic compounds in water: method development

Abstract: Persistent and mobile organic compounds (PMOCs) are highly soluble in water, thereby posing a threat to water resource quality. Currently, there are no methods that can accurately quantify guanidine derivative PMOCs, other than 1,3-diphenylguanidine (DPG) and cyanoguanidine (CG), in aqueous media. In this study, we developed a quantitation method that combines solid-phase extraction and liquid chromatography (LC)-tandem mass spectrometry to detect seven guanidine derivatives in aquatic environments and applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…Other chlorinated products, DTG, and 6PPD-quinone were not detectable in any of the samples. Observed concentrations of DPG in tap water in our study are similar to those reported in previous studies with one report from Japanese tap water showing maximum concentrations of 44 ng/L ( n = 2) and samples from a drinking water treatment plant from the Pearl River Delta region of China showing maximum concentrations of ∼36 ng/L …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Other chlorinated products, DTG, and 6PPD-quinone were not detectable in any of the samples. Observed concentrations of DPG in tap water in our study are similar to those reported in previous studies with one report from Japanese tap water showing maximum concentrations of 44 ng/L ( n = 2) and samples from a drinking water treatment plant from the Pearl River Delta region of China showing maximum concentrations of ∼36 ng/L …”
Section: Resultssupporting
confidence: 91%
“…DPG was found to occur in 100% of the samples (median = 4.31 ng/L, max = 32.6, min = 0.25 ng/L). While other studies have reported potential contamination from laboratory materials during sample processing and even DPG presence in ultrapure water, , all blank samples processed during this study were below the method reporting limit. Out of the five large molecular weight chlorinated byproducts studied, only three were detected, with CC15 also occurring in 100% of analyzed samples (median = 1.67 ng/L, max = 11.2, min = 0.29 ng/L).…”
Section: Resultsmentioning
confidence: 56%
“…With its ubiquitous usage and occurrence, the detection of polymer additive chemicals can be challenging. Many materials commonly used in laboratory operation, even if not in direct contact with samples, can be a source of contamination, as recently described with DPG being found in blank samples. , As an example, rubber materials such as the one used for vial closures, syringes, and even certain glove types can be a source of contamination. , To minimize such contamination sources, procedures that involve minimal sample handling can serve as an alternative. Constant development in LC-MS/MS instrumentation has also served to improve instrument limits of detection and robustness, reducing the need for sample preparation and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, one such polymer additive transformation product, 6PPD-quinone, has been associated with the mass mortality of fish species . Other additives such as 1,3-diphenylguanidine (DPG) are also found to occur in many drinking water sources due to urban runoff events and leaching from tire materials, with DPG being detected consistently among the highest concentrations for tire leachable organics. Additionally, DPG and 6-PPDQ uses in different applications can also be significant sources to the environment and to human exposure. , In tap water samples, DPG was found with a 100% detection frequency with a median concentration of 4.3 ng/L and was also associated with nontire-related source materials present in plumbing systems . In human urine, DPG was recently found with a detection frequency of 73% and 20% for children and adults, respectively, and at a median concentration of 0.05 ng/mL for children’s samples …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation